On the Impact of Channel Models for Indoor Localization - Garip, Deniz Ufuk Uras; Büyükçorak, Saliha; Kurt, Gunes Karabulut (IEEE, 2016)
It is a tough problem to determine and to model correctly, statistical properties of wireless communication channel. Especially for indoor wireless channel, It is more difficult. Because multipath effect becomes involved in. To make a good channel modeling for indoor localization systems enhances localization accuracy. Accuracy of localization depends on channel model that is used. Channel models give good results in theory but they are not enough good in real test environment. In this study, small scale fading and large scale fading are mentioned slightly and then It is shown experimentally that large scale fading is not enough good for indoor localization system. In the test section of this study, received signal strength measuring setup is developed by using defined software radio and then it is emphasized that inaccuracy of large scale fading for indoor localization via observed RSS values.
National Conference on Electrical, Electronics and Biomedical Engineering (ELECO) -- DEC 01-03, 2016 -- Bursa, TURKEY